Faktor-Faktor Abortus Provocatus dalam Perspektif Maqasid Syariah - Rahmat Ramadhan. Mz (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Various kinds of problems that exist today, arise one classic problem to the surface of modern Muslim society which refers to controversy, namely the case of abortion (abortion). The abortion of Provocatus is mostly done by mothers caused by several factors, including medical factors, and rape factors so that it does not have a small impact on death on the mother. This study was conducted to research factors. abortion provocateurs in the perspective of Maqasid Sharia. This research method involves analyzing literature studies for article materials that have something to do with the issues raised and then analyzing using the approach of Sharia Maqasid principles. In this study, it was found that there are factors that cause its occurrence. Abortion provocateurs is like a medical factor, and rape factors are permissible on emergency grounds. This research is expected to contribute to the study of Islamic family law and this research provides insight for the parties involved in understanding the factors that cause abortion provocateurs such as medical factors, and rape factors are permissible.